Liposomal Drug Delivery: Progress, Clinical Outlook, and Ongoing Challenges - Tiwari, Chanchal; Tomer, Jigyasa; Kumar, Dharmendra (Recent Advances in Drug Delivery and Formulation, 2024)
The liposomal drug delivery system is considered an advanced drug delivery technology for formulating lipid core nano-structured particles using lipids from natural and synthetic sources. Liposomes play a wide role in improving drugs with less solubility and greater toxicity profile. Liposomes have numerous advantages, such as enhanced drug loading, good biocompatibility, prolonged drug release profile, and better pharmacokinetic properties. Numerous attempts have been made in this field in the last few years, and lots of liposomal formulations are currently being sold all over the world, and few are under clinical study. Liposomal delivery technology improves the challenges of encapsulating poor soluble drugs and maintains the stability of the formulation, along with improving the challenges of in-vivo outcomes of liposomes. The present review discussed the brief outline of the liposome drug delivery system, the innovations in the clinical application, and the significant challenges in liposomal technology.
Keywords: liposomes